Efektivitas Pelatihan Public Speaking untuk Meningkatkan Kepercayaan Diri Mahasiswa Baru - Nugroho, Yudha; Muhammad Naufal Rifqi Fauzan; Muhammad Maftuh; Halilintar Sukma Cahya Jagad; Muhammad Irpan Rosyid; Muhammad Angga Pratama Putra (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
This study aims to determine the effect of public speaking on the subject's self-confidence, applying public speaking training to increase self-confidence in the subject. This type of research uses an experimental quantitative method with the type of experiment in the form of a true experiment. The characteristics of the research subjects are students of the Faculty of Psychology, Sarjanawiyata Tamansiswa University who take basic psychology courses in class A and have low self-confidence. Data collection techniques used in this study include observation, interviews, and questionnaires distributed through Google Form. The measuring instrument used in this study used a self-confidence scale. Based on the results of the study, it can be concluded that the results of the analysis of the post-test and pre-test using the paired sample t test obtained a value of p = 0.402 (p => 0.05) which means that there is no significant difference in the self-confidence of class A basic psychology students before and after training, but the average has increased from 128.80 to 140.00.